KLi2CO3F: a beryllium-free KBBF-type deep-UV carbonate with an enhanced interlayer interaction and large birefringence. Issue 14 (14th June 2022) - Wang, Qiang; Song, Wen; Lan, Yang; Cao, Liling; Huang, Ling; Gao, Daojiang; Bi, Jian; Zou, Guohong
Abstract : A beryllium-free deep-UV carbonate, KLi2 CO3 F, has been successfully designed through chemical co-substitution with KBBF as the prototype, which exhibits an enhanced interlayer interaction and enlarged birefringence. Abstract : KBe2 BO3 F2 (KBBF) with a perfect honeycomb hexagonal layered structure is the sole practical deep-ultraviolet (DUV) nonlinear optical material which could generate DUV coherent light through direct frequency doubling. However, the layered growth habit and the toxicity of Be severely hinder its extensive applications. Herein, a non-centrosymmetric fluoride carbonate, KLi2 CO3 F, was successfully developed via chemical co-substitution with KBBF as the prototype. KLi2 CO3 F preserves the structural merits of KBBF, containing neatly arranged infinite planar [Li2 CO3 F2 ]∞ layers. In particular, compared with the weak interlayer K–F electrostatic attraction in KBBF, KLi2 CO3 F presents a stronger interlayer binding energy induced by the shorter and stronger Li–F bonds, which effectively overcomes the layered tendency of crystal growth. Simultaneously, KLi2 CO3 F exhibits a large birefringence of approximately 0.102@546 nm and a short ultraviolet absorption edge down to 190 nm, indicating that it is a promising DUV birefringent material.